Installing large-scale community infrastructure: Homeowners' preferences toward notification and recourse. Issue 3 (27th May 2017) - Wadley, David; Elliott, Peter; Han, Hoon
Abstract: Large-scale infrastructure siting comes with few manuals about breaking bad news and offering recourse to affected communities. As an example, the installation of high voltage overhead electricity transmission lines (HVOTLs) is invariably contested and divisive. This article analyzes notification to affected parties and their pathways to advice. The medical, clinical, and organizational management literature enables creation of a multi-stage model to discover relevant preferences. From a survey of 600 homeowners in Queensland, Australia, binomial and multinomial logistic regressions indicate that: (a) personal visitation by authorities is preferred by older residents, those employed, and those concerned about visual, noise, and safety effects of HVOTLs; and (b) middle-aged respondents are likely to approach electricity corporation representatives or local council or planning officers, while those employed or holding hierarchical worldviews will often have little idea about avenues of assistance. The findings should inform infrastructure placement and other difficult situations in community development.